Analisis Efisiensi Perbankan Syariah Pada Masa Pandemi Covid-19 Menggunakan Data Envelopment Analysis (DEA) - Fredi Setyono; Yussufia Nur Azizah Istiqomah; Shila Ilmundhita; Abdul Mujib (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2021)
This study aims to determine the efficiency of Islamic banking in the face of a pandemic at BRI Syariah, BJB Syariah, BCA Syariah and Bank Syariah Bukopin. This study uses quantitative data using secondary data from the monthly financial reports of Islamic banks for 2020 at BRI Syariah, BJB Syariah, BCA Syariah and Bank Syariah Bukopin. This study uses Data Envelopement Analysis (DEA). The variables in this study use the input variables of capital, assets, labor costs and output variables of musyarakah financing, mudharabah financing and distribution of income. The results showed that some banks initially experienced 100% efficiency and during the pandemic experienced inefficiency or experienced a decrease in efficiency. BRI Syariah must experience a decrease in efficiency (inefficiency) after the pandemic in June, July, August 2020 and November 2020 with the CRS model and the June-August 2020 VRS model. The lowest point for BRI Syariah for the CRS model is 98.70% and for the VRS model it is 99.10%. BJB Syariah must experience a decrease in efficiency (inefficiency) due to the pandemic in April 2020, decreased in the CRS in April 2020 and the VRS Model from August 2020 to November 2020. The lowest point for BJB Syariah for the CRS model is 97.00% and for VRS model at 97.80%. BCA Syariah from April 2020 to September 2020, for CRS and VRS models, it is known that there is a reduction in performance (inefficiency) from the target that should have been achieved. The lowest point for the BCA Syariah for the CRS model is 94.80% and for the VRS model it is at 95.50%. March 2020 to November 2020 Bank Syariah Bukopin CRS and VRS models were ineffective due to the pandemic. Bank Syariah Bukopin's lowest point for the CRS model is at 95.50% and for the VRS model at 95.60%.